Compilation of maize technology components in acid dry land, Tanralili District. Issue 1 (April 2020) - Tabri, F; Syafruddin,; Aqil, Muhammad
Abstract: Compilation of Maize Technology Components in Acid Dry Land, Tanralili. The research objective is to obtain a combination of technological components that are suitable for maize plants. The experiment used a Randomized Block Design (RBD) consisting of 5 treatment combinations which were repeated three times to obtain 15 experimental units, namely: (A. Legowo (50-100) x 20 cm location-specific based on PUJS (N 235 kg, P 75 kg and K 75 kg ha −1 ) + BO 2t ha −1 ., (B). Legowo (50-100) - 20 cm + 2/3 site-specific based on PUJS + BO 2t ha −1 + POC Agrodeks 2l ha −1 ., (C) Legowo (50-100) - 20cm + Specific location based on PUJS + POC Product 2 l ha −1 ., (D). Legowo (50-100) - 20 cm + Specific location based on PUJS + organic matter 2 t ha −1 + POC Agrodeks 2 l ha −1 ., (E). Farmer Technology (80 x 40cm) 2 tan / hole (200 kg Urea and Ponska 100 kg ha −1 ). The further test used is the Advanced Test of Duncan's Multiple distance with a real level 5 % The results showed D treatment with Legowo planting system (50 x 100 cm) x 20 cm, location specific with 2 t ha −1 organic matter and liquid fertilizer Agrodek 2l ha −1 gave the best yield of 7.76 t ha −1, C treatment of planting system Legowo (50-100 cm) x 20 cm, location specific with liquid organic fertilizer Agrodek 2l ha −1 without using organic matter only yields 6.69 t ha −1 .